REAPPROPRIATION OF ELEVATED HIGHWAY RESIDUAL SPACE THROUGH GREEN INFRASTRUCTURE PLANNING - Mohamed Anuar, Mohamed Ikhwan Nasir; Abdullah, Saiful Arif (PLANNING MALAYSIA, 2020)
Kuala Lumpur City’s demand for a better connectivity has led to the vast development of elevated highways. This has caused the formation of residual spaces underneath megastructures. Previous studies indicated that these residual spaces triggered issues from dumping of debris to crimes. Aimed at exploring the typologies and reappropriation of these spaces through green infrastructure planning, three methods were utilised in this study: site observation, document analysis and expert interview. Results from the study showed that there were two main typologies of residual spaces, namely: (1) easily accessible and (2) hard to access spaces. The interview sessions with the experts suggested that suitable green infrastructure elements, such as play lots, recreational lots and community gardens were regarded as suitable for Typology 1. However, semi-natural areas and functional landscapes were viewed as suitable for Typology 2. It is hoped that the understanding of the typologies of residual spaces underneath elevated highways and its appropriation through green infrastructure planning could lead to a more sustainable use and management of urban space thus viewing it as an important urban resource.